A brief communication of shispar glacier surge in 2018, hunza river basin, Pakistan - Hussain, Alamgeer (International Journal of Advanced Geosciences, 2019)
Glacier surging is a common phenomenon in the Karakoram region, but the driving mechanisms, their occurrence and its relation to a changing climate remain are unclear. In this study, we use Sentinel imagery to quantify advancement of the Shispar glacier during a surge in 2018. Results reveal that Shispar glacier starts rapid surging from Jun 2018. The peak surge is in August 2018. Our data reveal that glacier dammed the Hassanabad stream as result lake formation in upstream area and drainage of the lake also blocked. The surging is continuing and size of newly formed glacier lake is also increasing day by day. Currently, the inflow to lake is very low due to low melting (negative temperature) from the upstream glacier. This inflow of glacier meltwater will be an increase in the summer season, which may grow in lake size and could pose threats to downstream settlements and infrastructure (irrigation channels, powerhouses and bridge at Karakoram Highway (KKH) in the case of a sudden breach in the form of glacial lake outburst flood (GLOF). Currently the damages the powerhouse channel and damage the irrigation channel of Aliabad Hunza. This study recommended that there is a need for monitoring of glacier lake size and blockage area using remote sensing data i.e. satellite images and UAV.Â Â